2000
DOI: 10.1530/eje.0.1420557
|View full text |Cite
|
Sign up to set email alerts
|

Familial growth hormone deficiency with mutated GHRH receptor gene: clinical and hormonal findings in homozygous and heterozygous individuals from Itabaianinha

Abstract: Objective: To characterize clinically and hormonally the syndrome of autosomal recessive familial growth hormone deficiency (FGHD) recently identified in Itabaianinha, Sergipe, Brazil, caused by a novel mutation (mt) that inactivates the growth hormone-releasing hormone receptor (GHRH-R) gene. Design: Clinical and hormonal evaluations were performed in 21 FGHD individuals (mt/mt group) aged 8 to 63 years, 13 heterozygotes for the GHRH-R mutation (wt/mt group) and 5 homozygotes for the wild type (wt) allele (wt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 15 publications
1
18
0
1
Order By: Relevance
“…Other reports have suggested a reduction of stature and lower serum IGF-I levels in heterozygous in comparison with homozygous normal individuals (17,28). Our finding of lower IGF-I levels in the heterozygous group may indeed confirm a reduction in GH secretion.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Other reports have suggested a reduction of stature and lower serum IGF-I levels in heterozygous in comparison with homozygous normal individuals (17,28). Our finding of lower IGF-I levels in the heterozygous group may indeed confirm a reduction in GH secretion.…”
Section: Discussionsupporting
confidence: 79%
“…MRI studies of these patients have been done in a limited number of cases (18, 20, 22 -25, 27), and have never included heterozygous carriers. As heterozygous carriers of GHRHR mutations have been reported to have lower serum insulin-like growth factor-I (IGF-I) than normal subjects (17,28), it is conceivable that they may have a pituitary size that may be intermediate between normal and affected subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GH-naive adults and children from this kindred have very low serum GH and IGF-I, reduced fat free mass, an increase in percentage of fat mass (FM), increased waist/hip ratio, increased total and LDL-cholesterol, and C-reactive protein (CRP) levels, and increased systolic blood pressure, but no insulin resistance and no evidence of pre-mature atherosclerosis (14 -17). In a preliminary study, HTZ subjects have been reported to have lower serum IGF-I than HMZ normal (18), but the small number of subjects and their heterogeneous age compared with controls prevented the drawing of firm conclusions. Here we have studied a significantly larger number of subjects HTZ for the mutation and compared them with age-and sex-matched controls.…”
mentioning
confidence: 99%
“…O quadro clínico e laboratorial dos indivíduos homozigotos é o da deficiência isolada de GH, similar ao dos outros indivíduos com mutações no gene do GHRHR, com função tireoideana e níveis de cortisol normais e fertilidade preservada. Já os indivíduos heterozigotos da população de Itabaianinha apresentam estatura similar à dos indiví-duos não portadores da mutação (18).…”
Section: Deficiência Isolada De Gh ("Nanismo Hipofisário")unclassified